Stranger Times. Heterotemporality and the Spiritual Experience of Illness - Pannofino, Nicola (Italian Sociological Review, 2024)
As highlighted in the medical humanities and narrative medicine the onset of a severe pathology constitutes a biographical disruption that on the one hand alters the patient’s temporal perspective throughout the therapeutic process, and on the other can trigger existential and spiritual questions and needs. The direct connection between temporality and spirituality in the subjective experience of illness is, however, little investigated in the sociological literature. Based on the analysis of personal illness narratives collected through qualitative interviews using the creative technique of time-box with cancer patients in Piedmont, this article shows how the relation with the disease is inscribed as an “other” time or “heterotemporality” in the patient’s life course, producing estranging effects on identity and agentivity from which emerges a spirituality focused on time as a resource for coping with suffering. These results can provide indications for implementing spiritual care strategies in healthcare and clinical contexts.